My Choice: Women's Contraceptive-Use Autonomy in Bangladesh. Issue 4 (2nd October 2019) - Blunch, Niels-Hugo
ABSTRACT: Using a nationally representative household survey for two cohorts of married women, this study examines women's contraceptive-use autonomy (CUA) incidence and correlates in Bangladesh, focusing on the role of education. Previous research has examined the incidence and correlates of contraceptive use and of several dimensions of female autonomy but only rarely the intersection of the two – that is, CUA. This study finds that women from the younger cohort are far more likely to have complete autonomy over contraceptive use than women from the older cohort. Detailed decompositions reveal that the improvement in education across cohorts is the main correlate of the improved generational CUA gap. Health knowledge, especially knowledge that the use of condoms can help avoid contracting HIV/AIDS, is part of the transmission mechanism between women's education and women's CUA but also exerts an additional influence on CUA.